Evaluation of the prevention of parent to child transmission program in a rural tertiary care hospital of West Bengal, India - Mandal Sukanta; Bhattacharya Rudra; Chakraborty Manasi; Pal Partha; Roy Samir; Mukherjee Gautam (Wolters Kluwer Medknow Publications, 2010)
Background: In India, 67,500 infants acquire HIV infection yearly due to mother to child transmission. Objective: The objective was to assess the operational aspect of the Prevention of Parent to Child Transmission (PPTCT) program in a tertiary care hospital and explore its bottleneck. Materials and Methods: A 5-year (2004-2008) prospective evaluation study was conducted among the pregnant women attending Obstetrics Department of a rural tertiary care hospital, since the year of implementation. Indicators were used according to UNAIDS/WHO guideline. Results: Out of 40,140 registered pregnant women, 23,812 were counseled of which 19,794 were agreed to undergo HIV testing and 111 were found HIV positive with a prevalence of 0.56%. Overall HIV counseling and testing rates were 59.32% and 83.13%, respectively. The nevirapine (NVP) dispensing rate of the mother and newborn were 29.72% and 85.4%, respectively. At 18 months of age, 85% babies were found HIV negative in the mother baby pair who received NVP with absolutely formula feeding but it was 42.8% without such intervention. Conclusion: Majority of the pregnant women who came to the labor room directly were deprived of the program (PPTCT) coverage. Although the HIV testing rate reached the WHO target which was excellent, but the NVP dispensing rate lagged far behind.